2020
DOI: 10.3390/catal10050541
|View full text |Cite
|
Sign up to set email alerts
|

Biomorphic Fibrous TiO2 Photocatalyst Obtained by Hydrothermal Impregnation of Short Flax Fibers with Titanium Polyhydroxocomplexes

Abstract: A biomimetic solution technology for producing a photocatalytic material in the form of biomorphic titanium oxide fibers with a hierarchical structure using short flax fiber as a biotemplate is proposed. The impregnation of flax fibers intensified under hydrothermal conditions with a precursor was performed in an autoclave to activate the nucleation of the photoactive TiO2 phases. The interaction between precursor and flax fibers was studied by using infrared spectroscopy (IR) and differential scanning calorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…The fibrous photocatalysts were prepared by calcination of the impregnated biotemplates in air in an electric furnace at 600 °C for 30 min. The calcination temperature was in accordance with our previous study that revealed the best photocatalytic activity for fibrous TiO 2 samples was prepared at 600 °C [ 28 ]. The Ti/Ce oxides denoted as TiO 2 –3% Ce and TiO 2 –5% Ce, where 3 and 5 wt.% were the Ce(NO 3 ) 3 ∙6H 2 O concentrations in the precursor solutions.…”
Section: Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The fibrous photocatalysts were prepared by calcination of the impregnated biotemplates in air in an electric furnace at 600 °C for 30 min. The calcination temperature was in accordance with our previous study that revealed the best photocatalytic activity for fibrous TiO 2 samples was prepared at 600 °C [ 28 ]. The Ti/Ce oxides denoted as TiO 2 –3% Ce and TiO 2 –5% Ce, where 3 and 5 wt.% were the Ce(NO 3 ) 3 ∙6H 2 O concentrations in the precursor solutions.…”
Section: Methodssupporting
confidence: 87%
“…The morphologies of the biotemplated TiO 2 –3% Ce and TiO 2 –5% Ce samples were studied by SEM, see Figure 2 . The SEM images of flax fiber and TiO 2 samples were published previously in [ 28 ]. The particles of all the photocatalysts had a similar fibrous structure replicating the texture of the flax template.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations